The WEGAS / GEA IV Geophysical Survey in eastern and southern Dronning Maud Land - Eagles, Graeme; Ruppel, Antonia; Steinhage, Daniel; Jokat, Wilfried; Läufer, Andreas; Jacobs, Joachim (26th International Congress on Polar Research, 2015)
The Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI) and the Federal Institute for Geosciences and Natural Resources (BGR) collected around 150 hours of new gravity, magnetic and ice-penetrating radar data from east and south of Princess Elisabeth station in Dronning Maud Land between 2013 and 2015. Survey lines were spaced 10 km apart. The 2013/2014 and 2014/2015 used different gravimeters; a LaCoste and Romberg AirSea gravimeter (LCR) at constant barometric altitude and a Gravimetric Technologies GT2A gravimeter at constant ground separation. Both surveys used a Scintrex Cs-3 caesium vapour magnetometer mounted in a tail boom with compensation for the airframe calculated using a fuselage-mounted three-component fluxgate magnetometer. The GT2A gravity data reflect the effects of short-wavelength density contrasts between basement rocks and the ice sheet more reliably than the LCR data. Cross-over analysis suggests the repeatability of data collection with the GT2A lies at the sub-milliGal level. A broad subglacial channel that separates eastern Sør Rondane from the Yamato Belgica Mountains is evident in the gravity data. In the south of the survey region, the data reveal a dendritic pattern of subglacial valleys that converge towards the SW. Strong NS-trending magnetic anomalies coincide with the Yamato-Belgica Mountains. Further west, subtler ESE-trending anomalies confirm proposals that the SE Dronning Maud Land province continues into the region south of eastern Sør Rondane. An unexpected feature of both data sets is the apparent termination of the anomaly patterns associated with the province at a NNW-trending anomaly running south of Princess Elisabeth.
Keywords: Dronning Maud Land; geofysikk; geovitenskap

Modern foraminifera assemblages in the Amundsen Sea Embayment - Jernas, Patrycja Ewa; Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Forwick, Matthias; Rasmussen, Tine Lander; Mackensen, Andreas; Schröder, Michael; Smith, James; Klages, Johann Philipp; Szczucinski, W (31st geological winter meeting: Vinterkonferansen 2015, 2015)
The West Antarctic Ice Sheet (WAIS) is considered the most unstable part of the Antarctic Ice Sheet. As the WAIS is mostly grounded below sea level, its stability is of great concern. A collapse of large parts of the WAIS would result in a significant global sea-level rise. At present, the WAIS shows dramatic ice loss in its Amundsen Sea sector, especially in Pine Island Bay. Pine Island Glacier (PIG) is characterised by fast flow, major thinning and rapid grounding-line retreat. Its mass los over recent decades is generally attributed to melting caused by the inflow of warm Circumpolar Deep Water (CDW). Future melting of PIG may result in a sea level tipping point, because it could trigger widespread collapse of the WAIS, especially when considering ongoing climate change.
Keywords: Sørishavet; geologi; innlandsis; klimaendringer

Modern foraminifera assemblages in the Amundsen Sea Embayment - Jernas, Patrycja Ewa; Kuhn, Gerhard; Hillenbrand, Claus-Dieter; Rasmussen, Tine Lander; Forwick, Matthias; Mackensen, Andreas; Schröder, Michael; Smith, James; Klages, Johann Philipp (EGU General Assembly 2015, 2015)
The West Antarctic Ice Sheet (WAIS) is considered the most unstable part of the Antarctic Ice Sheet. As the WAIS is mostly grounded below sea level, its stability is of great concern. A collapse of large parts of the WAIS would result in a significant global sea-level rise. At present, the WAIS shows dramatic ice loss in its Amundsen Sea sector, especially in Pine Island Bay. Pine Island Glacier (PIG) is characterised by fast flow, major thinning and rapid grounding-line retreat. Its mass los over recent decades is generally attributed to melting caused by the inflow of warm Circumpolar Deep Water (CDW). Future melting of PIG may result in a sea level tipping point, because it could trigger widespread collapse of the WAIS, especially when considering ongoing climate change.
Keywords: Sørishavet; geologi; innlandsis; klimaendringer

Lateral extrusion at the Eastern margin of the East African-Antarctic Orogen in Dronning Maud Land - Ruppel, Antonia; Läufer, Andreas; Jacobs, Joachim; Elburg, M; Krohne, N; Eagles, Graeme; Mieth, Matthias; Jokat, Wilfried; Damaske, Detlef; Lisker, Frank (26th International Congress on Polar Research, 2015)
The geology of Sør Rondane has been the focus of intense research and occupies a key position for reconstructing the late Neoproterozoic to early Paleozoic geodynamic evolution in eastern Dronning Maud Land (DML). Sør Rondane appears to be located close to the supposed intersection of the East African-Antarctic Orogen (EAAO) and the Kuunga Orogen. The western part of Sør Rondane is subdivided in two distinct terranes. The amphibolite to granulite-facies NE terrane is mainly composed of metasupracrustal rocks, with detrital zircon ages in part younger than 750 Ma, deposited on older basement of unknown, possibly Rayner-type, crust (Shiraishi et al., 2008). Metamorphism has been dated by U-Pb on zircon at ca. 640-600 Ma and amphibolite-facies retrogression dated at ca. 590-530 Ma. The SW terrane is subdivided by the Main Shear Zone (MSZ) into two lithothectonic units, i.e. Pan- African greenschist- to granulite-facies metamorphic rocks with “East African” affinities in the N and a Rayner-age early Neoproterozoic gabbro-tonalite-trondhjemite-granodiorite (GTTG) complex with “Indo-Antarctic” affinities in the S. The GTTG complex has suffered Pan-African greenschist- to lower amphibolite-facies thermal overprint, but also contains large domains with only weak deformation except for its northern margin close to the MSZ. The deformation there is related to high shear strain along this structure. New zircon crystallisation ages of the GTTG cluster around 1000-930 Ma. It is interpreted to have formed along a juvenile oceanic arc, in which the wide age range might indicate a long-lasting accretionary orogen. The MSZ is characterized by a right-lateral sense of movement and high-strain ductile deformation under peak amphibolite-facies conditions. The structure can be traced over a distance of ca. 120 km between Lågkollane in the W and Lunckeryggen in the E and reaches several hundred meters in width. The MSZ cannot be traced further to the W where it seems to terminate at the north-eastern border of the NW-SE oriented prominent magnetically defined SE DML Province. The north-eastern border zone may coincide with a significant dextral shear zone that runs from the Schirmacher Oasis into the region S of Sør Rondane (Schirmacher- Rondane Lineament). The SE DML Province most likely consists of Rayner-age (1000-900 Ma) crust with evidence of intense Pan-African reworking indicated by new geochronological data and was part of a large Tonian Oceanic Arc Super Terrane (TOAST). The continuation of the MSZ into eastern Sør Rondane and beyond is not clear either, since it appears to terminate at a N-S oriented region with low magnetic signatures (central Sør Rondane corridor) that is possibly related to extensional tectonics. Crosscutting relationships with dated magmatic rocks bracket the activity of the MSZ between Latest Ediacaran to Cambrian times (c. 560- 530 Ma). Based on new combined aeromagnetic and structural results from a four-seasons survey of the greater Sør Rondane region, we propose that the crustal structural architecture of eastern DML and is strongly influenced by N-directed (with Africa/Antarctica restored to its original position in Gondwana) lateral extrusion of the EAAO. This process was likely driven by the combination of (i) indentation of the SE DML block towards the conjugate stable Kalahari- Grunehogna cratonic foreland, (ii) extensional collapse of the previously (c. 580-550 Ma) thickened and gravitational instable crust of central DML, and (iii) large-scale tectonic escape of crustal blocks in eastern DML along major shear zones such as the Schirmacher Rondane Lineament and MSZ towards an unconstrained yet unknown region at a lateral position of the EAAO.
Keywords: Dronning Maud Land; geologi

Review of the low-temperature thermochronological data from the Dronning Maud Land Mountains, East Antarctica - Sirevaag, Hallgeir; Jacobs, Joachim; Ksienzyk, Anna Katharina; Dunkl, István (31st geological winter meeting: Vinterkonferansen 2015, 2015)
The paleo-topography of East Antarctica is highly relevant for the development of the East Antarctic ice-sheet. This ice-sheet originated probably as small ice caps and in the elevated areas of the cratons in East Antarctica around the Eocene/Oligocene boundary. East Antarctica contains three mountain ranges: the latitudinal Dronning Maud Land Mountains (DML), the longitudinal Transantarctic Mountains (TAM) and the sub-glacial Gamburtsev Mountains (GM). The 1500 km long, coast-parallel Dronning Maud Land Mountains probably resulted in a significant amount of precipitation prior to the initiation of the 34 Ma glaciation history of East Antarctica. Thus, the paleo-topography should be used as an important input parameter for the glaciation history.
Keywords: Dronning Maud Land; geologi